A Novel Opioid-Sparing Analgesia Following Thoracoscopic Surgery: A Non-Inferiority Trial - Sun JJ; Xiang XB; Xu GH; Cheng XQ (Dove Medical Press, 2023)
Jing-jing Sun,1,* Xiao-bing Xiang,2,* Guang-hong Xu,1 Xin-qi Cheng1 1Department of Anesthesiology, The First Affiliated Hospital of Anhui Medical University, Hefei, People's Republic of China; 2Department of Anesthesiology, The Cancer Hospital of the University of Chinese Academy of Sciences (Zhejiang Cancer Hospital), Hefei, People's Republic of China*These authors contributed equally to this workCorrespondence: Xin-qi Cheng; Guang-hong Xu, Department of Anesthesiology, The First Affiliated Hospital of Anhui Medical University, 218 Jixi Road, Hefei, Anhui, 230022, People's Republic of China, Tel +86-0551-62922344, Fax +86 0551 62923704, Email ay_mz_cheng@126.com; xuguanghong2004@163.comPurpose: This randomized, non-inferiority study aimed to observe the feasibility of opioid-sparing analgesia based on modified intercostal nerve block (MINB) following thoracoscopic surgery.Patients and Methods: 60 patients scheduled for single-port thoracoscopic lobectomy were randomized to the intervention group or control group. After MINB was performed in both groups at the end of the surgery, the intervention group received patient controlled-intravenous analgesia (PCIA) of dexmedetomidine 0.05 μg/kg/h for 72 h after surgery, and the control group received conventional PCIA of sufentanil 3 μg/kg for 72 h. The primary outcome was a visual analog scale (VAS) on coughing 24 h after surgery. Secondary outcomes included the time to first analgesic request, pressing times of PCIA, time to first flatus, and hospital stay.Results: There was no difference in the cough-VAS at 24 h (median [interquartile range]) between the intervention group [3 (2- 4)] and control group [3 (2- 4), P = 0.36]. The median difference (95% CI) in the cough-VAS at 24 h was [0 (0 to 1), P = 0.36]. There was no significant difference in the time to first analgesic request, pressing times of PCIA, and hospital stay between groups (P > 0.05). A significant decrease in time to first flatus was observed in the intervention group (P < 0.01).Conclusion: Opioid-sparing analgesia provided safe and analogous postoperative analgesia with a shortened time to first flatus, compared with sufentanil-based analgesia in thoracoscopic surgery. This might be a novel method recommended for thoracoscopic surgery.Graphical Abstract: Keywords: opioid-sparing, intercostal nerve block, dexmedetomidine, sufentanil, opioid consumption, thoracoscopic surgery